Antibiotic Resistant Genes in Multidrug-Resistant Extended-Spectrum ?-lactamase-Producing E. coli Isolated from Children’s Samples - sliai, Salam; Abo-Amer , Aly E.; Moubasher , Hani (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Antimicrobial resistance was declared by the World Health Organization (WHO) in 2014 as the greatest threat for human and veterinary medicine.The development of resistance in E. coli may be due to haphazard use of antibiotics, plasmid-mediated genes,i.e. blaCTX-M, blaSHV, blaOXA. This work was aimed to detect the antibiotic resistant genes in multidrug-resistant extended-spectrum ?-lactamase-producing E. coli from samples of children. 90 samples from chidren were collected. blaTEM, blaSHV, blaOXA, blaCTX-M and blaVEB resistance genes in drug-resistant E. coli were investigated. The blaTEM, blaSHV and blaCTX genes were detected in E.coli isolates. blaTEM genes were found to be in all isolates. The blaSHV gene was detected in 14.28% of the isolates. The blaCTX-M gene was detected in 71.42% of the isolates blaOXA and blaVEB genes were not detected in any sample.The resistant genes sequences of the E.coli isolates from urine, blood, skin ande ndotracheal tube were deposited in the DDBJ/EMBL/GenBank nucleotide sequence databases.The resistance genes sequences of the Escherichia isolates are greatest closely associated to those of Escherichia coli.